O-H center dot center dot center dot O-bridged dimers linked via C-H center dot center dot center dot O and C-H center dot center dot center dot pi interactions in 4,6-di-O-benzyl-myo-inositol 1,3,5-orthoformate - Manoj, Kochunnoonny; Devaraj, Subramanian; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Acta Crystallographica Section C-Crystal Structure Communications, 2005)

Short S=O center dot center dot center dot C=O contacts associate diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate in their inclusion complexes - Manoj, Kochunnoonny; Sureshan, K. M.; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Crystal Growth & Design, 2005)
Diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate are linked via short S=O&BULL;&BULL;&BULL; C=O contacts ranging from 2.890 to 3.140 &ANGS; (sum of the van der Waals radii of O and C atoms 3.22 &ANGS;) in all the inclusion complexes formed with organic guest solvents having a C2 symmetry. Although a search for S= O&BULL;&BULL;&BULL; C=O interactions in the CSD showed a sizable number of structures, this communication recognizes its significance for the first time in the formation of molecular assemblies. In all the crystals in the present study except the solvent-free form, the S=O bond points almost perpendicularly to the Csp2 atom of the C=O group. This was also the most frequently observed geometrical approach in CSD analysis. The solvent-free form shows dimer formation via C-H&BULL;&BULL;&BULL; O interaction, which has longer S=O&BULL;&BULL;&BULL; C=O contacts.

Cu(I)-catalyzed cycloaddition of constrained azido-alkynes: access to 12- to 17-membered monomeric triazolophanes incorporating furanoside rings - Ray, A.; Manoj, Kochunnoonny; Bhadbhade, Mohan M.; Mukhopadhyay, R.; Bhattacharjya, A. (Tetrahedron Letters, 2006)
A strained monomeric 12-membered triazolophane was formed by the Cu(I)-catalyzed intramolecular cycloaddition of an azide to an alkyne having a constrained tether incorporating ail aromatic ring and a furanoside ring. Similar cycloadditions of azido-alkynes having ester, furanoside and peptidic tethers led to the formation of monomeric triazolophanes of higher ring sizes. (c) 2006 Elsevier Ltd. All rights reserved.

Subtle crossover from C-H center dot center dot center dot O to S=O center dot center dot center dot C=O short contacts in the association of diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate upon format - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Crystal Growth & Design, 2006)
Diastereomers of 2,4(6)- di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoformate associate via weak interactions to form ``head-to-head'' dimers in their crystals. Molecular association through C-H center dot center dot center dot O short contacts do not leave any void for the guest inclusion, while association through S=O center dot center dot center dot C=O bridging produces pseudopolymorphs. Three crystalline modifications are observed for the title compound: form I, monoclinic P2(1), without any guest solvent, and solvated forms II and III, that belong to monoclinic space groups P2(1) and C2, respectively. A majority of solvates, which include pyridine, dichloromethane, benzene, tetrahydrofuran, and cyclohexanone as guests, belong to form III. All these guests have 2-fold symmetry axes ( C2) with their electron count within 40-62 electrons; guest selectivity experiments indicate that planar aromatic guests ( pyridine, benzene) bind better to the host molecules as compared to nonplanar guests ( dioxane, cyclohexanone). The molecular packing that is created thorough channels in the crystal ( avoiding interpenetration of the layers) are of interest because of their potential application in molecular separation by forming selective inclusions. The diastereomeric association via S=O center dot center dot center dot C=O dipolar short contacts, a consistent feature observed in all the solvates, is thought to have relevance in the binding of sulfonyl drugs to the C=O moieties of the receptor proteins.

Different interaction motifs of dipolar S = O center dot center dot center dot C = O contacts that associate diastereomers of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-7,7-dimethyl-2-oxo-bicyclo[2.2.1]heptan-1-ylmethyl]-sulfonyl-myo-inositol 1,3,5-ortho-acetate - Manoj, Kochunnoonny; Gonnade, R. G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Acta Crystallographica Section C‐Structural Chemistry, 2007)
Diastereomeric mixtures of 2,4(6)-di-O-benzoyl-6(4)-O-[(1S)-10-camphorsulfonyl]-myo-inositol 1,3,5-orthoesters associate in their crystal structures via different geometries of S=O...C=O short contacts, depending upon the substitution. A comparison of the dimeric association in the orthoacetate and orthoformate (solvated) derivatives shows a sheared parallel motif of dipolar S=O...C=O contacts bridging the former, whereas perpendicular S=O...C=O contacts occur in the latter. The title compound, C32H34O11S, is chiral, owing to the presence of the camphor moiety.

Dipolar S=O center dot center dot center dot C=O and C-H center dot center dot center dot O interactions in the molecular organization of 4,6-di-O-acetyl-2-O-tosyl-myo-inositol 1,3,5-orthoesters - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Acta Crystallographica Section C-Crystal Structure Communications, 2009)
In the absence of conventional hydrogen bonding, the molecules of 4,6-di-O-acetyl-2-O-tosyl-myo-inositol 1,3,5-orthoformate, C(18)H(20)O(10)S, (I), and 4,6-di-O-acetyl-2-O-tosyl-myo-inositol 1,3,5-orthobenzoate, C(24)H(24)O(10)S, (II), are associated via C-H center dot center dot center dot O interactions. Molecules of (II) are additionally linked via dipolar S=O center dot center dot center dot C=O contacts. It is interesting to note that the sulfonyl O atom involved in the dipolar S=O center dot center dot center dot C=O contacts does not take part in any other interaction, indicating the competitive nature of this contact relative to the weak hydrogen-bonding interactions.

Isostructural molecular strings linked via conserved dipolar (ether) O center dot center dot center dot C=O short contacts in conformational polymorphs of racemic 2,4-di-O-acetyl-6-O-tosyl-myo-inositol 1,3,5-orthoesters - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (CrystEngComm, 2009)
Conformational dimorphs of racemic 2,4-di-O-acetyl-6-O-tosyl-myo-inositol 1,3,5-orthoformate and its orthoacetate analogue were characterized using single crystal X-ray diffraction, thermal analysis and hot-stage microscopy techniques. In these polymorphs, the tosyl group adopted different conformations due to the rotation about the O-S bond. A significant variation in the torsion angle for the tosyl group (similar to 56 degrees) was observed for Form II crystal of the orthoformate derivative, which exhibited an intramolecular dipolar S=O center dot center dot center dot C=O (sulfonyl-carbonyl) short contact. An interesting feature in all conformational polymorphs is the formation of an isostructural string (despite the differences in the orientation of the tosyl group) linked via dipolar (ether) O center dot center dot center dot C=O contacts, which is further stitched by other weak interactions to form different layers in their crystal lattice.

Conformational polymorphism in racemic 2,4-Di-o-Benzoyl-6-o-Tosyl myo-Inositol 1,3,5-Orthoacetate - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, M. S. (Journal of Structural Chemistry, 2010)
The title compound, C(29)H(26)O(10)S, yields two conformational polymorphs concomitantly from dichloromethane-methanol mixture; the major polymorph grows as plates (Form I, monoclinic, P2(1)/n) and the minor polymorph grows as needles (Form II, triclinic, P-1). The two forms differ mainly in orientation of the tosyl group. In Form I, sulfonyl oxygen of the tosyl group makes intermolecular C -HaEuro broken vertical bar O interactions, whereas the same group in Form II is involved in an intramolecular short dipolar S=OaEuro broken vertical bar C=O (sulfonyl-carbonyl) contact. The molecular organization and the influence of various weak non-covalent interactions that stabilize these conformers in the crystal lattices are discussed.
Keywords: Conformation; crystal structure; dipolar interactions; Inositol; non-covalent interactions; polymorphism; sulfonyl-carbonyl contact

Syntheses, characterisation and vapour pressure of metallo-organic titanium precursor for MOCVD applications - Arockiasamy, S.; Manoj, Kochunnoonny; Bhadbhade, Mohan M.; Mallika, C.; Nagaraja, K. S. (Inorganica Chimica Acta, 2010)
Metallo-organic complexes of titanium such as [Ti(bzac)(2)(O(i)Pr)(2)] (1) and [Ti(bzac)(2)en(O(i)Pr)(2)] (2) were synthesised using 1-phenyl-1,3-butanedione (bzac) and the Schiff's base ligand N, N0-ethylene-bis(1-phenyl-1,3-butanediimine) [(bzac)(2)en]. A novel ligand 1-phenyl-3-N-(2-hydroxy-2-methylethylimino)-1-butanone (bzac1a2pol, 3) synthesised by condensing benzoylacetone (bzac) with 1-amino-2-propanol (1a2pol) was used in the synthesis of the complex bis(1-phenyl-3-N-(2-hydroxy-2-methylethylimino)-1-butanoato)titanium (IV), [Ti(bzac1a2pol)(2), 4]. These complexes were synthesised by replacing the isopropoxy group (O(i)Pr) of titanium tetra-isopropoxide, Ti(O(i)Pr)(4) by the appropriate ligands. Complexes 1, 2 and 4 were characterised for their volatility/thermal stability using TG/DTA and complex 4 was found to be volatile giving a residue of similar to 5.0% (TG) at 377 degrees C and similar to 3.0% (reduced pressure, 1 mbar) at 285 degrees C. Ligand 3 and its Ti complex 4 were characterised by (1)H NMR, (13)C NMR, elemental analysis, mass spectrometry and single crystal XRD. A value of 164.2 +/- 5.2 kJ mol(-1) for the standard enthalpy of sublimation (Delta H(sub)(0)) was evaluated for 4 from its vapour pressure. (C) 2010 Elsevier B. V. All rights reserved.
Keywords: MOCVD; Single crystal; Syntheses; Ti complexes; Vapour pressures; Volatile complexes

Solvent induced crystallization of 1,2,3,4(6),5-penta-O-acetyl-6(4)-O-[(1S)-10-camphor sulfonyl]-myo-inositol diastereomers associated via weak trifurcated C-H center dot center dot center dot O interactions - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (CrystEngComm, 2012)
The title compound produced three different types of solvent inclusion crystals having a conserved dimeric association via trifurcated C-H center dot center dot center dot O interactions between the diastereomers. These `dimeric' units are organized differently to produce three crystal types containing guest molecules. In type I and II, unit translated dimers created voids for guest inclusion, whereas in type III the guest sites were produced by helical association of dimers. Inclusion of dichloromethane gave two different types of crystals; however, we were unable to obtain unsolvated crystals of the title compound.

Highly efficient chiral resolution of DL-arginine by cocrystal formation followed by recrystallization under preferential-enrichment conditions - Iwama, Sekai; Kuyama, Kazunori; Mori, Yuko; Manoj, Kochunnoonny; Gonnade, Rajesh G.; Suzuki, Katsuaki; Hughes, Colan E.; Williams, P. Andrew; Harris, Kenneth D. M.; Veesler, Stephane; Takahashi, Hiroki; Tsue, Hirohito; et al. (Chemistry-A European Journal, 2014)
An excellent chiral symmetry-breaking spontaneous enantiomeric resolution phenomenon, denoted preferential enrichment, was observed on recrystallization of the 1:1 cocrystal of dl-arginine and fumaric acid, which is classified as a racemic compound crystal with a high eutectic ee value (>95%), under non-equilibrium crystallization conditions. On the basis of temperature-controlled video microscopy and in situ time-resolved solid-state (CNMR)-C-13 spectroscopic studies on the crystallization process, a new mechanism of phase transition that can induce preferential enrichment is proposed.
Keywords: Amino acids; chiral resolution; cocrystals; Crystal growth; phase transitions

Preferential enrichment of DL-leucine using cocrystal formation with oxalic acid under nonequilibrium crystallization conditions - Manoj, Kochunnoonny; Takahashi, Hiroki; Morita, Yoko; Gonnade, Rajesh G.; Iwama, Sekai; Tsue, Hirohito; Tamura, Rui (Chirality, 2015)
By utilizing the preferential enrichment (PE) technique, we achieved an improved enantiomeric resolution of DL-leucine (Leu) using a 1:1 cocrystal (DL-1) of DL-Leu and oxalic acid. The crystal structure analysis of DL-1 indicated the occurrence of a novel type of phase transition and subsequent preferential redissolution of one enantiomer from the resulting crystals into solution. Chirality 27:405-410 2015. (c) 2015 Wiley Periodicals, Inc.
Keywords: chiral resolution; cocrystal formation; leucine; phase transition; preferential enrichment

Five concomitant polymorphs of a green fluorescent protein chromophore (GFPc) analogue: understanding variations in photoluminescence with pi-stacking interactions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Nikam, Shrikant B.; Puthuvakkal, Anisha; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Acta Crystallographica Section B-Structural Science Crystal Engineering and Materials, 2020)
The synthetically modified green fluorescent protein chromophore analogue 3,4,5-trimethoxybenzylidene imidazolinone (1) yielded five polymorphs (I, II, III, IV, V) concomitantly irrespective of the solvent used for crystallization. The pentamorphic modification of 1 is solely due to the interplay of iso-energetic weak intermolecular interactions in molecular associations as well as the conformational flexibility offered by a C-C single bond, which connects the electron-deficient moiety imidazolinone with the electron-rich trimethoxybenzylidene group. A common structural feature observed in all the polymorphs is the formation of a `zero-dimensional' centrosymmetric dimeric unit through a short and linear C-H center dot center dot center dot O hydrogen bond engaging phenyl C-H and imidazolinone carbonyl oxygen. However, the networking of these dimeric units showed a subtle difference in all the polymorphs. The 2D isostructurality was observed between polymorphs I, II and III, while the other two polymorphs IV and V revealed only `zero-dimensional' isostructurality. The different fluorescence emissions of Form I (blue) and Forms II to V (yellow) were attributed to the differences in pi-stacking interactions. It shows that one can modulate the photophysical properties of these smart materials by slightly altering their crystal structure. Such an approach will aid in developing new multi-colour organic fluorescent materials of varying crystal structures for live-cell imaging and fluorescent sensing applications.
Keywords: green fluorescent protein; hydrogen bonds; isostructurality; photoluminescence; pi-stacking; Polymorphs

Crystal structure analysis of highly efficient chiral resolution of (RS)-arginine-fumaric acid cocrystal under preferential enrichment conditions - Manoj, Kochunnoonny; Takahashi, Hiroki; Iwama, Sekai; Gonnade, G. Rajesh; Tsue, Hirohito; Tamura, Rui (Journal of Molecular Structure, 2021)
Two new hydrate cocrystals, (RS)-arginine-fumaric acid-H2O ( 2 ) and (S)-arginine-2 fumaric acid-H2O ( 3 ), were obtained by the slow evaporation of the saturated aqueous ethanol solution of a 1:1 mixture of S-enriched arginine (33% ee) and fumaric acid or (S)-arginine and fumaric acid, respectively. Cocrystals 2 and 3 possess an isostructural molecular organization containing homochiral 1D chains of arginine sim-ilar to that of the anhydrous cocrystal of (RS)-arginine-fumaric acid ( 1 ). The latter showed an efficient ``preferential enrichment (PE)'', a unique spontaneous enantiomeric resolution phenomenon by simple recrystallization from the highly supersaturated solution. The formation of unstable cocrystals 2 and 3 seems to have played a crucial role in the enrichment of arginine in the mother liquor under PE crystal-lization conditions. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: Arginine; cocrystals; crystal structure; Enantiomeric resolution; preferential enrichment

Polymorphs of green fluorescence protein chromophore analogue: fluorescence switching with thermal stimuli - Mali, Bhupendra P.; Dash, Soumya Ranjan; Biswas, Anupam; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Crystal Growth & Design, 2022)
Polymorphs of fluorescent organic materials offer significant implications in optoelectronics and advanced materials as they modulate photoluminescence properties. A slight alteration in the conformation/packing of molecules in the crystals shows variation in photoluminescence. This necessitates the polymorph screening of these materials to develop novel crystalline forms with distinct fluorescence emissions for broader application. In continuation of our work on the polymorph screening of Green Fluorescence Protein Chromophore (GFPc), we have synthesized a new imidazoline derivative, ethyl (Z)-2-(2-methyl-5-oxo-4-(3,4,5-trimethoxybenzylidene)-4,5-dihydro-1H-imi dazol-1- yl)acetate (1). Polymorph screening of 1 under different crystallization conditions revealed three polymorphs, Form I (needle), Form II (block), and Form III (polycrystalline material). Forms I and II are the outcome of solution crystallization, whereas Form III was produced from the melt crystallization of Forms I and II. DSC, HSM, and powder and single-crystal XRD studies indicate the conversion of Form I and Form III crystals to Form II crystals on thermal stimuli. The photoluminescence studies revealed cyan, yellow, and yellowish-green fluorescence emission for Forms I, II, and III crystals, respectively. The difference in photoluminescence could be due to the variance in aggregation modes like H-aggregation in Form I and J-aggregation in Form II crystals. Form I, Form II, and Form III crystals also showed irreversible thermal fluorescent switching from cyan-yellow-green due to polymorphic phase transitions. The study correlates the direct observation of the modulation of the excited-state transition under thermal stimuli in the crystalline phase. It will help augment the pace in the research of thermally responsive fluorescent materials.

Cocrystal approach to modulate the photoluminescent properties of a GFP chromophore analogue: role of halogen/hydrogen bonding in achieving a wide range of solid-state fluorescence emissions - Mali, Bhupendra P.; Dash, Soumya Ranjan; Annadhasan, Mari; Biswas, Anupam; Manoj, Kochunnoonny; Vanka, Kumar; Gonnade, Rajesh G. (Crystal Growth & Design, 2023)
Fine-tuning the photophysical properties of fluorescentorganicsolids is essential to attain multicolor displays and meet the demandfor futuristic light-emitting materials. Here, we report the tunableluminescence of a green fluorescent protein (GFP) chromophore analogue,3,4,5-TIA (A), based on the formation of two-component molecular cocrystalswith six different coformers. Coformers selected to synthesize thebinary cocrystals include 1,4-diiodotetrafluorobenzene (B), perfluoronaphthalene(C), 1,4-dibromotetrafluorobenzene (D), 2,3,5,6-tetrafluoroterephthalicacid (E), benzene-1,2,4,5-tetracarbonitrile (F), and benzene-1,2,4,5-tetracarboxylicacid (G). Interestingly, the cocrystals A center dot C and A center dot Fshowed molecular crystal polymorphism with a slight variation in fluorescence,revealing an aggregation-induced emission (AIE). A crystal structureanalysis showed the interplay of hydrogen bonding, halogen bonding,and aromatic pi-stacking interactions in associating neutralsolid components in the cocrystal. All of the novel cocrystals displayeda wide range of photoluminescence ranging from blue to dark orange.The time-dependent density functional theory (TD-DFT) calculationsindicate the changes in the energy level structures (HOMO to LUMO)in cocrystals that resulted in variations in fluorescence emission.The study aims to further understand the structure-propertyrelationship between molecular arrangement and photoluminescence. Cocrystals of a GFPc analogue with differentcoformers displayeda wide range of fluorescence emissions ranging from blue to dark orangewith varying quantum yields. With similar geometries of pi-stackinginteractions, hydrogen and halogen bonding have played a vital rolein fine-tuning the photoluminescence; halogen bonding leads to a blueshift, and hydrogen bonding results in a red shift.

Unravelling polymorphism-driven luminescence in GFP chromophore analogues: insights into the phase transition and morphology-dependent optical waveguide properties - Dabke, Niteen B.; Raut, Yash; Mali, Bhupendra P.; Pandya, Rinu; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Journal of Materials Chemistry C, 2024)
The advent of multi-emission organic solid-state materials in response to external stimuli has sparked the scientific community due to their potential application in developing sophisticated optoelectronic sensors and bioanalytical tools. This article presents green fluorescent protein chromophore (GFPc) analogue-based polymorphs exhibiting significantly different emissions due to various noncovalent interactions in the supramolecular environment and conformational alterations in the crystalline state. In both compounds (A and B), the polymorphs undergo monotropic thermal phase transitions that are characterized by DSC, HSM, and VT-PXRD techniques. The distinct fluorescent emission characteristics of these polymorphs demonstrated morphology-related optical waveguiding features. Specifically, the plate-type Form A1 emitted light with a 2D blue hue, while the needle-type Form A2 emitted light with a yellowish-green colour. Additionally, the impressive waveguiding capabilities of Form B1 were explored in both straight and singly/doubly bending configurations to facilitate fluorescence propagation. Consequently, there is significant interest in developing organic materials based on GFP chromophores, which exhibit low emission in solution but display multi-fluorescent emission in the solid state. These materials are promising for applications such as optoelectronic devices, security tags, live cell imaging, and fluorescent inks. Polymorphs of GFPc analogs A and B display differences in their optical waveguiding properties in 1D and 2D depending on the crystal shapes. Furthermore, Form B1 demonstrates efficient optical waveguiding capabilities even when the crystal is bent.

Synthesis and concomitant polymorphs of green fluorescence protein chromophore-anthracene-based fluorescent analogue - Mali, Bhupendra P.; Dabke, Niteen B.; Dash, Soumya R.; Biswas, Anupam; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Crystal Growth & Design, 2025)
Controlled variations in fluorescence properties hold significant promise for applications in optical sensors, bioimaging, and advanced display devices. However, constructing multicolor fluorescent systems remains a challenge. In this study, we demonstrate the development of multicolor fluorescence by generating polymorphs of a novel green fluorescent protein chromophore analogue, which exhibits distinct photoluminescence emissions in the solid state. The observed emission variations are attributed to differences in molecular conformation due to variations in pi-stacking interactions between the polymorphs. This offers a novel approach to designing materials with tunable fluorescence properties.

Switchable solid-state emission in GFP chromophore analogue cocrystals via competing AIE and ACQ pathways - Mali, Bhupendra P.; Dabke, Niteen B.; Sharma, Himanshu; Dash, Soumya Ranjan; Manoj, Kochunnoonny; Vanka, Kumar; Gonnade, Rajesh G. (CrystEngComm, 2026)
We present a crystal-engineering approach enabling switchable solid-state emission (green -> orange -> quenched) in GFP-chromophore analogue cocrystals. The coformer's electronic and supramolecular effect shifts the photophysical pathway: intramolecular CT in cocrystal-I (green) and cocrystal-III (quenched) and intermolecular CT in cocrystal-II, yielding orange emissions and highlighting cocrystallization's power for tunable luminophores.